Combined Pulmonary Fibrosis and Emphysema Syndrome: A New Phenotype within the Spectrum of Smoking-Related Interstitial Lung Disease - Karina Portillo; Josep Morera (Pulmonary Medicine)
Combined pulmonary fibrosis and emphysema (CPFE) is a recently defined syndrome, in which centrilobular and/or paraseptal emphysemas in upper lung zones coexist with pulmonary fibrosis in lower lobes in individuals. These patients have a characteristic lung function profile, with unexpected subnormal dynamic and static lung volumes, contrasting with a significant reduction of carbon monoxide transfer (DLco) and exercise hypoxemia. Pulmonary hypertension is highly prevalent in CPFE and is the leading determinant of death. Tobacco smoking has been proposed as the main factor in its etiology, though the pathophysiology and its natural history remain to be determined. High-resolution computed axial tomography is the mandatory tool to confirm the diagnosis. Currently, there is no consensus about its treatment since those published to date on this issue are limited to well-characterised series of cases; hence, a better understanding of this entity may help in the development of future therapeutic approaches.